A Policy Brief on Democratic Leadership: Partisan Versus Non Partisan Politics - Aciro-Lakor, Rita H. (Uganda Women’s Network, 2019)
This document is developed after discussion held over time as to whether individuals who work with NGO and be partisan and how this would affect their work or how they are perceived. The document is also intended to create understanding amongst pollution on the matters here discussed. To digest these issues, UWONET organized a think tank of members from Women’s rights organization to discuss and draw and understanding. This document therefore, focuses on drawing the thin line and understanding and the balance between Partisan versus and Non–Partisan Politics, a notion that has led to many to disengage with serious socio–economic and political matters of livelihood and development in the matters of national governance.